Neurophysiological Evidence of Motor Network Reorganization in Myotonic Dystrophy Type 1: A Pilot Magnetoencephalographic Study. Issue 1 (January 2019) - Formaggio, Emanuela; Del Felice, Alessandra; Turco, Cristina; Cudia, Paola; Baba, Alfonc; Bevilacqua, Francesca; Masiero, Stefano; Piccione, Francesco
Abstract : Purpose: Myotonic dystrophy type 1 is the most common muscular dystrophy in adults. Although brain involvement is well recognized, the relationship between cortical motor control and voluntary movement has not been sufficiently explored. This study aims at assessing magnetoencephalographic (MEG) rhythms at oscillatory and connectivity levels to map central motor control. Methods: Magnetoencephalographic data were acquired from healthy subjects and five myotonic dystrophy type 1 subjects during resting state and foot movement. Resting state EEG band power, event-related desynchronization/synchronization, functional connectivity, and network features (node strength and betweenness centrality) were estimated. A statistical comparison of these indexes between the two groups was run; a linear correlation between event-related desynchronization and motor performance was obtained. Results: Myotonic dystrophy type 1 subjects showed higher theta power over central motor regions and lower beta power over frontal areas, with a decrease of beta node strength over the dominant hemisphere and an increase of betweenness centrality over the vertex. Foot movement in the most impaired myotonic dystrophy type 1 subjects was inefficient in evoking event-related desynchronization. In less severely impaired participants, dominant foot movement was related to a bilateral sensorimotor event-related desynchronization. Conclusions: Results provide proof of a central dysfunction of movement. Identification of neurophysiological motor patterns in myotonic dystrophy type 1 could provide a guide for tailored therapy.